Pitt-Hopkins syndrome: report of a case with a TCF4 gene mutation - Orsini Alessandro; Mantellassi Ilaria; Bonuccelli Alice; Taddeucci Grazia; Tarantino Enrico (BMC, 2010)
Abstract Aims We will discuss the clinical and genetic diagnosis of a child with severe psychomotor delay, who at 3 years of age presented with paroxysms of hyperpnea-apnea and seizures unrelated to breathing anomalies. Methods The child underwent genetic (karyotype, FISH telomeres) and neuroradiological (cranial CT and MRI) tests, which proved to be normal. He came under our clinical observation at 3 years and 5 months of age. Due to severe psychomotor delay and facial dysmorphisms we completed the genetic investigations based on his clinical feature and analysis of the available literature. Results The presence of severe mental retardation associated with anomalous breathing pattern may suggest the Joubert and Rett syndrome, however these were excluded on the basis of clinical and genetic examination. Angelman syndrome, suspected for facial dysmorphisms and absent language, was also excluded because of the presence of a normal pattern of methylation at SNRPN locus. Another possible diagnosis was the Pitt-Hopkins Syndrome (PHS), characterized by severe mental retardation, breathing anomalies (paroxisms of hyperpnea-apnea), dysmorphisms and sometimes epilepsy. Haploinsufficiency of TCF4 gene located at 18q21.2 region has been recently identified as causative of this syndrome. In our patient the research of TCF4 mutation by the Institute of Human Genetics, University Hospital Erlangen (Germany), showed a de novo mutation. Conclusions The diagnosis of Pitt-Hopkins syndrome, an underdiagnosed cause of mental retardation, was based on clinical and genetic findings. Searching for TCF4 mutations is highly recommended when others overlapping syndromes was excluded. At our knowledge our patient is the first italian case of PHS diagnosed at molecular level.